To solve this system of equations using substitution, we'll first solve the first equation for y in terms of x:
y = 2x - 8
Next, we substitute this expression for y into the second equation:
3x - 4(2x - 8) = 7
3x - 8x + 32 = 7
-5x + 32 = 7
-5x = -25
x = 5
Now that we have found the value of x, we can substitute it back into the first equation to find y:
y = 2(5) - 8
y = 10 - 8
y = 2
Therefore, the solution to the system of equations is x = 5 and y = 2.
solve the system of equations using substitution
y = 2x - 8
3x - 4y = 7
1 answer